Cathodal transcranial direct current stimulation affects seizures and cognition in fully amygdala-kindled rats. (July 2013) - Kamida, Tohru; Kong, Shiqi; Eshima, Nobuoki; Fujiki, Minoru
Abstract : This study evaluated the effects of weak transcranial direct current stimulation (tDCS), a new non-invasive brain stimulation technique, on amygdala-kindled rats. The seizure severity, i.e. seizure stage, afterdischarge duration (ADD), and AD threshold (ADT) in the animals were measured one day after the last cathodal tDCS session, comparing with those of pre-treatment controls. Furthermore, the effects of cathodal tDCS on cognitive function were also studied by a water maze test (WMT) two days after the last tDCS session. Cathodal tDCS treatment significantly improved the seizure stage and decreased ADD together with elevated ADT one day after the last tDCS session. The treatment also showed significant improvement in the performance of WMT. The findings suggest that cathodal tDCS has anticonvulsive after-effects last at least for one day on the amygdale-kindled rats and positively affects cognitive performance.